Equivalence of vertical block linear complementarity problems and multi-objective programming problems - Chakraborty, B.; Biswal, M.P.; Nanda, S. (Journal of information & optimization sciences, 2010)
In this paper, Multi-objective Programming (MOP) approaches are proposed to deal with the feasible Vertical Block Linear Complementarity Problems (VLCP) and to look into the solvability and unsolvability of the VLCP. The characterization of an unsolvable VLCP is obtained via the existence of nonzero efficient point of the MOP problem. Also a perturbed problem is proposed if the VLCP is unsolvable for small disturbances in data. This perturbed problem is useful to construct the solvable VLCP corresponding to the original unsolvable VLCP. Examples are given to demonstrate the effectiveness of the results.